2005
DOI: 10.1017/s1481803500012914
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine teaching faculty perceptions about formal academic sessions: “What’s in it for us?”

Abstract: Background: Little is known about factors affecting emergency physician attendance at formal academic teaching sessions or what emergency physicians believe to be the benefits derived from attending these activities. Objectives: To determine what factors influence emergency medicine faculty attendance at formal academic rounds, what benefits they derive from attendance, and what differences in perceptions there are between full-time clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Of note, the intervention required only 90 minutes of residents' time. Previous work has shown that time away from clinical responsibilities is a significant impediment to education focused on communication skills [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the intervention required only 90 minutes of residents' time. Previous work has shown that time away from clinical responsibilities is a significant impediment to education focused on communication skills [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first formal structured discussion of the clinical education of EM residents, to our knowledge, by a group of EM educators. Other studies have surveyed EM faculty on teaching style and effective methods of teaching and have reported on challenges to teaching in the ED 25–27 . Surveys have also asked learners what they want from teachers and what they feel should be taught in the ED 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other EM studies, but differs from other medical specialties in which nonattendance is unrelated to professional or personal conflicts. 9 The 24-hour, 365-day scheduling, which requires EPs present in the emergency department, does not mesh easily with traditional 9 am to 5 pm academic scheduling.…”
Section: Discussionmentioning
confidence: 99%